Predicted Factors Related to Medication Compliance and Blood Pressure in Hypertension Patients - Faridah Baroroh; Imaniar Noor Faridah; Andriana Sari; Yosi Pratama Dewi (Journal of Pharmascience, 2026)
Nonadherence to antihypertensive medication is a key factor contributing to treatment-resistant hypertension. The main goal of hypertension treatment is to reduce morbidity and mortality by effectively lowering blood pressure. This study aimed to identify the factors influencing medication adherence and blood pressure regulation in patients with hypertension. This research utilized a retrospective cohort design. Data were gathered using the MARS questionnaire and patient medical records. The study sample consisted of hypertensive outpatients from five community health centers in the Special Region of Yogyakarta, Indonesia. Data analysis was performed using the Chi-square test. A total of 410 respondents met the inclusion criteria, with the majority being female (75.7%), 67.8% of patients adhered to their medication regimen, while 49.5% had controlled blood pressure. Difficulty remembering to take medication (p=0.010) and difficulty taking medication (p=0.049) were significantly associated with non-adherence. Age (p=0.001) and medication adherence (p=0.037) were also significantly associated with blood pressure control. The study's conclusion showed that adherence to taking medication and age are highly correlated to controlled blood pressure in hypertensive patients. Moreover, several factors related to compliance need to be identified to increase patient compliance and therapy outcomes for outpatient hypertension patients at the health center.